Taman Pendidikan Alquran bagi Ibu Rumah Tangga - Liwa Kartina Hapip (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2022)
There are many virtues of memorizing the Qur'an so many Muslims try to do it, including housewives. This study aims to determine which tahfidz program is suitable for housewives whose working hours are uncertain and must accompany their children. This study uses a type of field research using comparative qualitative methods, comparing the management of the tahfidz Al-Qur'an program for housewives in Saudi Arabia and in Indonesia. Based on the results of the study, it was found that the tahfidz Al-Qur'an model for housewives was one who could still be close to their children, carried out in a classroom located close to the participant's house, had educators besides memorizing the Qur'an who also mastered andragogy learning methods, the implementation every working day, there are various choices of classes according to the abilities of the participants, carried out in a place that is not only a place for teaching and learning but also socializing with other mothers. For operational funds, it is hoped that TPQ can be more independent so that they can make programs that are more interesting than the existing ones, and provide even better facilities that make participants comfortable in learning.AbstrakBanyak keutamaan menghapal Al-Qur'an sehingga banyak muslim berusaha melakukannya, tidak terkecuali ibu rumah tangga. Penelitian ini bertujuan untuk mengetahui program tahfidz yag cocok untuk ibu rumah tangga yang jam kerjanya tidak tentu dan harus mendampingi anak-anaknya. Penelitian ini mengunakan jenis penelitian lapangan mengunakan metode kualitatif komparatif, membandingkan pengelolaan program tahfidz Al-Qur'an untuk ibu rumah tangga di Arab Saudi dengan di Indonesia. Berdasarkan hasil penelitian didapat model tahfidz Al-Qur'an bagi ibu rumah tangga adalah yang tetap bisa dekat dengan anaknya, dilakukan di ruangan kelas yang letaknya dekat dari rumah peserta, memiliki pendidik selain hafal Al-Qur'an juga yang menguasai metode pembelajaran andragogi, pelaksanaanya tiap hari kerja, tersedia berbagai pilihan kelas sesuai kemampuan peserta dilakukan di sebuah tempat yang tidak hanya sebagai tempat belajar mengajar namun juga bersosialisasi dengan ibu-ibu lain. Untuk dana operasional diharapkan TPQ dapat lebih mandiri sehingga dapat membuat program yang lebih menarik dari yang sudah ada, serta menyediakan fasilitas lebih baik lagi yang membuat peserta nyaman belajar.